Information Technology Adoption And The Growth Of Small And Medium Enterprises In Greater Kampala Metropolitan Area, Uganda - Tukundane, Benson; Kibuuka, Muhammad; Sunday, Arthur (International Journal of Advanced Research and Publications, 2020)
Growth of Small and Medium Enterprises plays a major role in improving a country’s economic development. Whereas research identifies the role played by Information Technology adoption in improving the growth of organizations, much emphasis has been given to understanding large organizations in developed countries. This has left SMEs in developing countries prone to low growth and limited survival in the market with the contemporary competitive business environment. More so, SMEs contribute approximately 20% of GDP in most developing countries. Apparently, due to a weak link between Information Technology adoption and Growth of SMEs. In Uganda, it appears that there is need for a greater emphasis on studies that link information technology adoption and growth of SMEs. In this study a mixed methods approach and cross-sectional research design was used to establish the effect of information technology adoption and growth of small and medium enterprises in greater Kampala metropolitan area on a sample of 189 top administrators of SMEs. Findings revealed approximately a large correlation between information technology adoption and growth of SMEs. Linear regression results revealed that 42.2% of growth of SMEs according to this study was explained by variations in information technology adoption practices. As a result, this study recommends that SMEs ought to take advantage of the existing sophisticated and the ever varying information technologies in order to achieve their ultimate goal which is growth.
Keywords: Information Technology; Small And Medium Enterprises; Kampala Metropolitan